RESEARCH OF CHANGE IN FUEL CONSUMPTION USING ECO-DRIVING RULES - Bagavičius, Manvydas (PROFESSIONAL STUDIES: Theory And Practice, 2022)
Research examines the fuel consumption of a gasoline engine. Eco-driving is described in theoretical terms. The making of an additional fuel tank system is described which is used to accurately determine fuel consumption. Routes A-E have been developed and tested by driving the car conventionally and in accordance with the principles of eco-driving. Fuel consumption for all routes was obtained and fuel savings were calculated. The ecological and financial benefits of eco-driving have been calculated. Keywords: Eco-driving, ecology, fuel consumption, petrol engine, fuel system.